ANALISIS PENILAIAN KINERJA KEUANGAN PT BANK RAKYAT INDONESIA TBK, YANG TERDAFTAR DI BURSA INDONESIA - Daming , Sudirman; Widyawati, Widyawati (Universitas Ichsan Sidenreng Rappang, 2025)
Analysis of the Financial Performance Assessment of PT Bank Rakyat Indonesia Tbk, listed on the Indonesia Stock Exchange. This study aims to assess the financial performance of PT Bank Rakyat Indonesia Tbk, listed on the Indonesia Stock Exchange. Data collection used quantitative data obtained from the website of PT Bank Rakyat Indonesia Tbk, which is listed on the Indonesia Stock Exchange. The results of the study were obtained from the calculation of the Capital Adequacy Ratio (CAR), the Quality of KAP's Productive Assets, Net Profit Margin (NPM), Return on Assets (ROA), and the Liquidity Ratio (LDR). The results show that PT Bank Rakyat Indonesia Tbk, listed on the Indonesia Stock Exchange, has a HEALTHY predicate in the Capital, Asset, and Management aspects. It has a LESS HEALTHY predicate in the Earnings aspect, and an UNHEALTHY predicate in the Liquid aspect. Based on the research results, the researcher recommends that PT Bank Rakyat Indonesia Tbk, listed on the Indonesia Stock Exchange, continue to improve its business activities to maintain its health. And the importance of the CAMEL method as a reference for giving ratings to companies. Because the five CAMEL factors are the basic factors for measuring a bank's performance from all aspects.